Hyperuricemia and Impaired Renal Function: A Prospective Cohort Study - Noppawit Aiumtrakul; Puvanant Wiputhanuphongs; Ouppatham Supasyndh; Bancha Satirapoj (Karger Publishers, 2020)
Background: Related studies have demonstrated a relationship of elevated serum uric levels with a decline in kidney function. However, limited evidence exists in a Southeast Asian community-based population. Objective: The study aimed to examine the relationship between serum uric acid levels and impaired renal function. Methods: A prospective cohort study was conducted in the Thai army health checkup population between July 1, 2006 and December 31, 2012. Inclusion criteria included age older than 20 years and baseline estimated glomerular filtration rate (eGFR) over 60 mL/min/1.73 m2. Cox regression analysis was used to evaluate the association between incidence of impaired renal function and baseline serum uric acid quartiles. Impaired renal function was defined as eGFR <60 mL/min/1.73 m2 over 3 months. Results: A total of 9,534 participants (7,474 men and 2,060 women) were enrolled. Cox regression analysis revealed a significant association of serum uric acid level with impaired renal function in the whole population as the unadjusted hazard ratio (HR) (95% CI) of impaired renal function in second, third, and fourth quartiles were 2.1 (1.39, 3.17), 2.39 (1.6, 3.59), and 3.94 (2.71, 5.74), respectively, when compared with serum uric acid in the first quartile, respectively. After adjusting in 2 models, the HR still significantly persisted with similar magnitudes in all quartiles. Higher incidences of impaired renal function were observed among males than among females in all quartiles. Kaplan-Meier curve showed better renal survival rate in the lower quartile groups. Linear regression analysis showed that eGFR negatively correlated with serum uric acid (r = −0.213, p < 0.001). Conclusion: Our study suggests that an independent association exists of serum uric acid levels with the incidence of impaired renal function and renal progression in the Southeast Asian community-based population.